Winter Olympics: A tale of two countries - Seiler, S. (Sportscience, 1998)
Author gives a brief overview of Norwegian winter sports history and then looks at changes that may explain the sudden embarrassment of riches in Norwegian Olympic sport. He compares the situation and the performances of Norway and Sweden. He concludes that Norway's influx of economic support for hosting the 1994 Olympics in Lillehammer and a highly centralized sport development program may explain the differences in Olympic success of these two Scandinavian neighbors.